Elder Mice Exhibit More Severe Degeneration and Milder Regeneration in Temporomandibular Joints Subjected to Bilateral Anterior Crossbite - Zhang, Yuejiao; Xu, Xiaojie; Zhou, Peng; Liu, Qian; Zhang, Mian; Yang, Hongxu; Yu, Shibin; Zhang, Jing; Huo, Wanqiu; Zhao, Yali; Wang, Meiqing (Frontiers in Physiology, 2021)
Temporomandibular joints (TMJs) have a biomechanical relationship with dental occlusion. Aberrant occlusion initiates degenerative remodeling responses in TMJ condyles. Aging is a promoting factor of osteoarthritis (OA) development. The aim of this study was to assess the effect of aging on degenerative remodeling in TMJ condyles in response to occlusal biomechanical stimulation caused by the installation of aberrant prostheses and observe rehabilitation after their removal. The experiments involved 84 female C57BL/6J mice (42 at 6 weeks old and 42 at 28 weeks old). A bilateral anterior crossbite (BAC) model was developed, and the TMJs were sampled at 3, 7, and 11 weeks. BAC was removed at 7 weeks in a subset of mice, which accepted BAC treatment at 6 week of age, and maintained for another 4 weeks after BAC removal. TMJ changes were assessed with micro-CT, histomorphology, immunohistochemistry (IHC), and immunofluorescence staining assays. The results showed that BAC induced typical OA-like TMJ lesions that were more severe in the elder groups as evaluated by the acellular zones, clustered chondrocytes, fissures between cartilage and subchondral bone, reductions in matrix amount and the cartilage thickness as revealed by histomorphological measurements, and subchondral bone loss as detected on micro-CT images. IHC indicated significant increases in cleaved caspase-3-expressing cells and decreases in ki67-positive cells in the BAC groups. There were obvious age-dependent changes in the numbers of superficial zone cells and CD90-expressing cells. Supportively, cleaved caspase-3-expressing cells obviously increased, while ki67-expressing cells significantly decreased with aging. In the elder BAC groups, the superficial zone cells such as CD90-expressing cells were greatly reduced. At 11 weeks, the superficial zone cells were almost non-existent, and there were clear serrated injuries on the cartilage surface. BAC removal attenuated the degenerative changes in the condylar cartilage and subchondral bone. Notably, the rescue effect was more pronounced in the younger animals. Our findings demonstrate the impacts of aging on both TMJ degenerative changes in response to BAC and regenerative changes following BAC removal. The reduced number of chondro-progenitor cells in aged TMJ cartilage provides an explanation for this age-related decline in TMJ rehabilitative behaviors.